The impact of the level of focus on a change in the level of fear of falling during leading in competition climbing - Piepiora, Paweł; Kwieciński, Artur; Migasiewicz, Juliusz (Journal of Education, Health and Sport, 2019)
Background & Aim: The aim of this study was to determine whether the level of focus affects a person’s ability to overcome the fear of falling during leading in competition climbing. Matherial and Method: The subjects were members of the Polish competition climbing national team. The sample consisted of 30 climbers aged between 16 and 52 years. The study was conducted on the Eiger artificial climbing wall in Wrocław. The test methods used were Brickenkamp’s d2 Test of Attention and the authors’ original Scale of Fear of Falling Assessment. Results: An analysis of the data obtained demonstrated that the majority of men (66%) and women (66%) scored positively. At the same time, a minority (33%) of men scored above average on the d2 test and the same tendency was observed in women (25%). Across the whole group studied this results in 30% of persons who successfully dealt with fear and, simultaneously, demonstrated a high level of focus. Conclusions: It has been shown that there is no significant link between the level of focus and the ability to overcome the fear of falling during leading in competition climbing. The level of focus demonstrated may be directly related to how well a climber copes while tackling difficult routes, but it has no direct effect on overcoming his or her fear of falling.